Occurrence, source apportionment and source-specific risk assessment of antibiotics in a typical tributary of the Yellow River basin. (1st March 2022) - Wang, Linfang; Wang, Yifan; Li, Hua; Zhu, Yuen; Liu, Ruimin
Abstract: The spatial distributions, sources, and source-specific risk apportionments of 26 antibiotics (5 categories) in the Fenhe River basin were determined based on sample data. The results showed that antibiotics were widely distributed in the surface water. There were significant differences between the different types of antibiotics, and the highest mean concentration was that of the sulfonamide category (33.74 ng/L), accounting for 36% of the total antibiotic concentration. Spatially, all antibiotics were mainly detected in the middle and downstream areas. The ecological risk assessment results showed that the significant risk rate of antibiotics accounted for 70% and was mainly distributed in the downstream area; however, the risks differed between the 5 categories. Quinolone antibiotics exhibited the highest significant risk rate, reaching 100%. The ecological risk associated with sulfamethoxazole was the highest among all detected antibiotics. The following five main factors influenced the antibiotic concentrations: aquaculture, pharmaceutical wastewater, livestock discharges, domestic sewage, and sewage treatment plants. Among these, pharmaceutical wastewater sources contributed the most (35%) to the total antibiotic concentration, and were distributed throughout the river. Although livestock discharges were not the main reason for the high level of ecological risk, these discharges were highest at certain sites in the midstream region. Different pollution sources posed different levels of ecological risk to the Fenhe River basin, the highest of which was pharmaceutical wastewater with a significant risk rate of 58%. Graphical abstract: Image 1 Highlights: Antibiotics were widely detected and mainly distributed in mid and downstream. The overall significant risk (high, medium, and low) rate of antibiotics was 70%. Among identified five sources, pharmaceutical wastewater contributed the most. Risk levels of different sources were related to the concentration and toxic effects.